The Effect Of Recruitment And Selection On The Competence And Performance Of Managers Of Village Business Entity (Bumdes) In Kampar Regency Riau Province - Ardha, Annisa; Hendriani, Susi; Fitri, Kurniawaty (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
Abstract: This study aims to determine the effect of recruitment and selection on the competence andÂ perfomance of Village-Owned Enterprises (BUMDes) manager in Kampar Regency, Riau Province. In this study, there are four variables, namely Recruitment (X1), Selection (X2), Competence (Y1) and Performance (Y2). The population in this study is the BUMDes manager in Kampar Regency. The method of determining the number of samples was obtained through purposive sampling technique (30 BUMDes Managers from 229 BUMDes in Kampar Regency based on criteria). The data collection was gained through interviewing, observing and distributing questionnaires to respondents. While, in terms of data analysis this study used was two-stage regression analysis namely simple and multiple regression, the quality test of research instruments , test classic assumptions and hypotheses that were processed using the SPSS program (Statistical Program Society Science) version 21. The result shows that: 1) recruitment has a positive and significant effect on the competencies of BUMDes manager, 2) selection has a positive and significant effect on the competencies of BUMDes manager, 3) recruitment and selection has a positive and simultant effect the competence of BUMDes manager, 4) competence has a positive and significant effect on the performance of BUMDes manager.Â Keywords: Recruitment, Selection, Competence, Performance.